Prioritizing Elective Surgical Cases During a Pandemic or Global Crisis: The Elective-Pediatric Orthopedic Surgical Timing (E-POST) Score. Issue 4 (9th April 2022) - Truong, Walter H.; Ramo, Brandon; Birch, Craig; Dodwell, Emily; Johnson, Megan; Lebel, David E.; McIntosh, Amy; Miller, Dan; Snyder, Andrew; Sturm, Peter; Guillaume, Tenner
Abstract : Background: As the first wave of the COVID-19 pandemic stabilized and resources became more readily available, elective surgery was reinitiated and hospitals realized that there was little guidance on how to prioritize elective cases. Methods: A prioritization tool was formulated based on clinically relevant elements and previous literature. Nine pediatric orthopaedic surgeons from North American institutions evaluated 25 clinical scenarios on 2 occasions separated in time. Intra-rater and inter-rater reliability were calculated [intraclass correlation coefficient (ICC)]. Surgeons also ranked the importance of each element and how confident they were with scoring each factor. Results: Intra-rater ICC for total score showed good to excellent consistency; highest at 0.961 for length of stay (LOS) and lowest at 0.705 for acuity. Inter-rater ICC showed good to excellent agreement for American Society of Anesthesiologists score, LOS, duration of surgery, and transfusion risk and moderate agreement for surgical acuity and personal protective equipment (PPE) use. Transfusion risk and duration of surgery were deemed least important, and surgeons were least confident in scoring PPE and transfusion risk. Based on findings, the novel Elective-Pediatric Orthopedic Surgical Timing (E-POST) score for prioritizing elective cases was developed, consisting of 5 factors: surgical acuity, global health status, LOS, duration of surgery, and PPE requirement. Conclusions: The E-POST numeric total score or subscore may help objectively prioritize elective cases during a global crisis. Level of Evidence: Level V.